2020
DOI: 10.1021/acs.macromol.0c01686
|View full text |Cite
|
Sign up to set email alerts
|

Site-Selective, Organoboron-Catalyzed Polymerization of Pyranosides: Access to Sugar-Derived Polyesters with Tunable Properties

Abstract: A new class of sugar-derived polyesters has been synthesized, using organoboron-catalyzed acylation to generate linear macromolecules having pyranoside units enchained with a uniform 3,6-connectivity. The method provides access to welldefined polymers bearing pendant hydroxyl groups, from commercially available diacid chlorides and readily accessible pyranoside feedstocks. Variation of the configuration of the pyranoside (α-manno, α-galacto, or β-galacto) and the identity of the aglycon has been conducted, ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Based on the proposed mechanism, a more electron-rich borinic acid would display higher catalytic activity due to the enhanced nucleophilicity of active borinate species 67 . Screening phenylborinic acid derivatives with a variety of substituents led to the identification of heteraborinine-derived borinic acids ( 70 and 71 ) as more efficient catalysts for regioselective sulfonylation, glycosylation, sulfation, and acylation of carbohydrates (Figure a). For example, 3- O -benzylation of methyl α- l -rhamnopyranoside ( 36 ) proceeded in similar yield with smaller catalyst loading (from 10 mol % to 5 mol %) in shorter reaction time (from 48 to 24 h, Figure b) than the reaction using 57 as a catalyst. These heteraborinine-derived borinic acids showed lower association constants with diol substrates, but DFT calculation suggested that their borinate adducts had higher nucleophilicity due to incorporation of the borinic acid group into a 6π electron system and the resulting decreased Lewis acidity of the boron center.…”
Section: Covalent Bond-forming Catalysis With 12-diolsmentioning
confidence: 99%
“…Based on the proposed mechanism, a more electron-rich borinic acid would display higher catalytic activity due to the enhanced nucleophilicity of active borinate species 67 . Screening phenylborinic acid derivatives with a variety of substituents led to the identification of heteraborinine-derived borinic acids ( 70 and 71 ) as more efficient catalysts for regioselective sulfonylation, glycosylation, sulfation, and acylation of carbohydrates (Figure a). For example, 3- O -benzylation of methyl α- l -rhamnopyranoside ( 36 ) proceeded in similar yield with smaller catalyst loading (from 10 mol % to 5 mol %) in shorter reaction time (from 48 to 24 h, Figure b) than the reaction using 57 as a catalyst. These heteraborinine-derived borinic acids showed lower association constants with diol substrates, but DFT calculation suggested that their borinate adducts had higher nucleophilicity due to incorporation of the borinic acid group into a 6π electron system and the resulting decreased Lewis acidity of the boron center.…”
Section: Covalent Bond-forming Catalysis With 12-diolsmentioning
confidence: 99%
“…74 Analogous to known reactions using tin reagents, complexation of the borinic acid activated the bound oxygen atoms as nucleophiles (Figure 4), with selectivities based on dipole−dipole interactions along with steric interference to favor one of the two bound oxygen atoms. These reaction conditions have also been applied to polymerization reactions to produce sugar-based polyesters 103 and to the site-selective formation of sulfate esters 104 and sulfamate esters 105 of sugars. Boronic acids displayed significantly reduced catalytic activity and selectivity in these reactions.…”
Section: ■ Acylationmentioning
confidence: 99%
“…Organoboron is a class of compounds have a broad range of applications in materials science such as dynamic covalent materials, [1][2][3][4] optical and electrochemical sensors, [5][6][7] nanomaterials, [8][9][10][11][12] functionalized biomaterials, [13][14][15][16] natural products, [17][18][19] agrochemicals, [20][21] and pharmaceuticals chemistry as the active drugs molecules [22][23][24][25][26][27][28][29] for instances Velcade, Ninlaro etc. (Figure 1).…”
Section: Introductionmentioning
confidence: 99%